Зближення законодавства України з правовою системою Європейського Союзу - Гомонай, В.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
The article is devoted to the processes of legal integration of Ukraine into the European Union. Special attention in this research is given to illumination of the theoretical legal problems of adaptation of the legislation of Ukraine to the legislation of the European Union. Legal basis and maintenance of cooperation between Ukraine and EU are characterized, conditionand prospects of their development and perfection are analyzed. Рассматриваются теоретико-правовые предпосылки сближения правовой системы Украины и права ЕС. Определяются понятийно-категориальная сущность и способы согласования норм национального права и права, исследуются особенности гармонизационного механизма сближения законодательства Украины с правовой системой Европейского Союза, а также основные пути правового наполнения евро-интеграционного курса Украины.